Association between blood eosinophil count and Duchenne muscular dystrophy severity and prognosis: a retrospective cohort study - Zhi Jiang; Hongmei Liao; Liwen Wu; Wenjing Hu; Liming Yang; Bo Chen; Zeshu Ning; Jingwen Tang; Rong Xu; Mei Chen; Feng Guo; Shulei Liu (BMC, 2023)
Abstract Background Duchenne muscular dystrophy (DMD) is a rare hereditary muscular disease. The role of eosinophils in DMD has not been clarified. This study aims to evaluate the association between peripheral blood eosinophil count and severity and prognosis of DMD. Methods A retrospective cohort study was performed for 145 DMD patients between January 2012 and December 2020. Clinical data of 150 healthy children were collected as a control group. Logistic regression and Cox regression analyses were used to explore the influences of eosinophil count on DMD severity and prognosis. Results Eosinophil count in DMD group was lower than the control group (Z = 2.163, P = 0.031). It was negatively correlated with Vignos scale score, Spearman correlation coefficient was p = 0.245, P = 0.040 (at admission), p = 0.137, P = 0.032 (at follow-up); was a protective factor for high Vignos scale score at admission [odds ratio (OR) = 0.038, 95%CI: 0.002-0.752, P = 0.032] and follow-up (OR = 0.033,95%CI: 0.001-0.121, P = 0.039). The Cox regression analysis indicated that elevated eosinophil count was correlated with better therapeutic efficacy for DMD patients [hazard ratio (HR) = 2.218, 95%CI: 1.154-3.924, P = 0.016]. Conclusion Eosinophil count in peripheral blood was correlated with the severity of DMD. It could indicate the therapeutic efficacy and prognosis of DMD patients to a certain extent. Eosinophils may be a potentially valuable biomarker or therapeutic target for DMD.